Assessing neuroinflammation and inflammasome activity in mouse models of Down syndrome - Farrell, Clíona; Mumford, Paige; Salih, Dervis; Toomey, Christina; Fisher, Elizabeth; Wiseman, Frances K (Alzheimer's & dementia, 2021)
Background Down syndrome (DS) is caused by trisomy of chromosome 21 (Hsa21) and is a leading genetic cause of Alzheimer’s disease. Neuroinflammation is altered in the post‐mortem brain of people with DS, with altered microglial morphology and upregulated proinflammatory cytokines, including IL‐1β. IL‐1β is produced by inflammasome activity activating caspase‐1 which cleaves and releases active IL‐1β. We hypothesize that IL‐1β levels are raised in the DS brain via upregulation of inflammasome activity, which persists when people with DS develop AD. Method Levels of 10 cytokines IL‐1β, TNFα, IFNγ, IL‐6, IL‐2, IL‐4, IL‐5, IL‐10, IL‐12p70 and KC/GRO were measured (MSD) in the 3‐month hippocampus of a panel of segmental duplication models of DS, Dp1Tyb, Dp2Tyb, Dp3Tyb, Dp9Tyb and Dp17Yey. These models have a duplication on one chromosome of a number of orthologues for Hsa21 genes. Result Raised IL‐1β abundance was identified in the hippocampus of the Dp1Tyb mouse, which has an additional copy of 148 mouse orthologues for Hsa21 genes. No difference in IL‐1β or any other cytokines measured were identified in the Dp3Tyb (39 genes duplicated), Dp9Tyb models (76 genes duplicated), Dp2Tyb (33 genes duplicated) or Dp17Yey (19 genes duplicated). Conclusion Raised IL‐1β in the Dp1Tyb brain is a multigenic phenotype, caused by having 3 copies of more than one gene/region of Hsa21. Next, we will prepare organotypic hippocampal slice cultures from the Dp1Tyb model and stimulate these with LPS, nigericin and amyloid‐β to understand how having three copies of Hsa21 orthologues modulates the neuroinflammatory and inflammasome response.